Anti-osteoarthritic Effects of an Herbal Composition LI73014F2 on Interleukin-1β-induced Primary Human Articular Chondrocytes - Kim, Hae Lim; Lee, Hae Jin; Lee, Dong-Ryung; Choi, Bong-Keun; Yang, Seung Hwan (Molecules (Basel, Switzerland), 2020)
Osteoarthritis (OA) is one of the most well-characterized joint diseases and is associated with chondrocyte inflammation, metalloproteinase upregulation and apoptosis. LI73014F2 is a novel composition prepared from aqueous extract of Terminalia chebula fruit, alcohol extract of Curcuma longa rhizome, and Boswellia serrata extract at 2:1:2 ratio. Earlier studies have shown that LI73014F2 inhibits cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX) activities, and attenuates clinical symptoms in OA subjects. In the present study, we evaluated the protective anti-inflammatory and anti-apoptotic effects, as well as the underlying mechanisms, of LI73014F2 in interleukin (IL)-1β-induced inflammation in human primary chondrocytes. Human chondrocytes were treated with LI73014F2 (0, 12.5, 25 and 50 μg/mL) in IL-1β (10 ng/mL)-containing chondrocyte growth medium for 24 h. Cell viability was assessed using an MTT assay. The pro-inflammatory mediator, inflammatory cytokines, MMPs, apoptosis-related proteins, mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) signaling pathways protein expression levels were detected by western blot analysis. The results demonstrated that LI73014F2 normalized the expressions of COX-2, mPGES-1, PGE2, 5-LOX, LTB4, IL-1β, TNFα, IL-6, MMP-2, MMP-3, MMP-9, MMP-13, Bax/Bcl-2, cleaved caspase-9 and -3, cleaved PARP, phospho-NF-κB p65 and phospho-p38 MAPK proteins in IL-1β-induced primary human chondrocytes. Moreover, the data suggested that LI73014F2 reduced IL-1β-induced inflammation and apoptosis, at least partially via the inhibition of the NF-κB/MAPK signaling pathway. In conclusion, the present findings provide the molecular basis of the anti-OA efficacy of LI73014F2.